The Repeated Word Yarad In the Book of Jonah: Points, Pattern, And Purpose - Prabowo, Paulus Dimas (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
The Book of Jonah contains the word 'yarad' four times, which constitutes one of the recurring motifs in the text. Its usage is often interpreted as indicative of multidimensional degradation and is even associated with foreshadowing Christ's redemptive work. However, a critical question arises: What was the author of the Book of Jonah attempting to underscore through the repeated inclusion of the word 'yarad'? This study aims to delve into the occurrences of 'yarad' in the Book of Jonah through stylistic analysis to discern patterns, thereby elucidating the author's intent in employing these repetitions throughout the narrative. The methodology employed is stylistic analysis, with particular attention paid to the repetitive element. Consequently, discernible patterns emerge in 1:3b, 1:3c, 1:5b, and 2:6a, which exhibit a tendency towards diminishment yet encompass contrasts and pivotal moments. Consequently, it becomes evident that the author of the Book of Jonah strategically employs the word 'yarad' four times to accentuate contrasts, degradation, and pivotal shifts.